Impactos da agricultura 4.0 nos pequenos produtores rurais de uma cooperativa do agronegócio no Paraná - Pereira, Sabrina Aparecida (2023)
Technological innovation has been implemented more intensively in Brazilian agriculture in recent decades. These technologies can be seen in machines, pesticides, applications, and even in the soil and seeds used. This wave of technological innovation in agriculture, known as Agriculture 4.0, affects all rural producers, including small producers, who may have fewer resources to adapt to changes. Thus, this study aims to analyze the impacts that Agriculture 4.0 generates for small rural producers who participate in an agroindustrial cooperative in the Campos Gerais region, in the state of Paraná. To achieve this objective, a Systematic Literature Review will be carried out, using the Methodi Ordinatio methodology. Additionally, a census field survey will be carried out with 200 small cooperative members, members of the cooperative objective of study, aiming to investigate how these small cooperative members have adhered, adapted and reacted to the technologies of Agriculture 4.0.